Dinamika Perbedaan Pendapat Ulama Terkait ketentuan al¬-Maur ṹṣ atau Harta bersama bagi Janda dan Duda Setelah Formulasi Kompilasi Hukum Islam. - Muhammad Fadhlan Is (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
One of the important studies in Islamic family law is the provision of inheritance. Inheritance provisions are often a source of disputes within the family, especially in determining who is entitled to receive an inheritance. One form of progress in Islamic law in Indonesia is the formulation of the Compilation of Islamic Law. Article 97 of the Islamic Law Compilation stipulates that the share of inheritance for widows and widowers states that "The divorced widow or widower is each entitled to half of the joint property as long as it is not specified otherwise in the marriage agreement. The application of this article has received a response from the clergy and mass organizations in the country. The type of research used in this research is library research. The primary data source looks at the results of the Muhammadiyah Tarjih Council Decisions and the Decisions of Bahsul Masa'il Nahdhatul Ulama after 1991. The results of the study show the fact that there is a response to the acceptance of joint property provisions in KHI. First, from Bahtsul Masa'il NU, it was stated that the provisions for shared assets in KHI had not been accepted, divided automatically 50:50 because there was no ṣigat in the consent and qabul when the marriage contract, the automatic distribution of 50:50 was invalid because all the heirs who were still alive had not agreed. Both of the Muhammadiyah Tarjih Council can accept joint property provisions. According to Muhammadiyah, shared assets can be attributed to the concept of syirkah abdan (kongsi) in classical fiqh. Because husband and wife both contribute energy, help to meet household needs. Another reason is because the provisions on shared assets can be categorized as 'urf authentic which has been widely practiced in various regions in Indonesia.